Relationship between the adherence to the mediterranean diet, nutrient intake and anthropometric measurements for adult individuals living in Cyprus - Yıldırım, Ayşen; Dağcılar, Kamil; Güngör Başaran, Asiye Yeter; Harmancıoğlu, Begüm; Elmas, Cemre; İçten, Çağla; Kahır, Nuriye; Gökensel Okta, Pınar (Progress in Nutrition, 2022)
Objective: The Mediterranean diet (MD) is recommended as a nutrition model that exhibits preventive characteristics against several chronic diseases. The present study aimed to determine the adherence to MD and the relationship among adherence to MD, nutrition, anthropometric measurements of adult individuals living in Cyprus.Methods: The study participants comprised 705 individual. The face-to-face interviews with them comprised general information, the MD adherence score, frequency of food consumption, anthropometric measurements. The data collected were evaluated using the appropriate statistical analyses.Results: Of the study participants, 35.7% had low adherence to MD, 57.1% had medium adherence, and only 7.2% had high adherence. We observed that participants who had low adherence to MD had higher body weight, body fat ratio, body lean tissue mass (p < 0.05). Daily fiber, monounsaturated-fatty-acid intakes were lower (p < 0.05). In addition, we observed that individuals with high adherence to MD had higher vitamin A and D intakes than the participants (p < 0.05).Conclusion: Similar to the results in the literature, we observed that individual adherence to MD might create positive effects on some anthropometric measurements and some nutrient intakes. Therefore, MD is considered to be a healthy diet based on those results.